Analisis Waiting Time Kapal dan Approach Time sebagai Indikator Kinerja Pelayanan Operasional Pelabuhan pada Pelabuhan Tanjung Intan Cilacap - Hari Sucahyowati; Dedeh Suryani (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2023)
The performance of port operational services can be measured by various indicators. One of the indicators is Waiting Time or ship waiting time. Waiting time and approach time are calculated from the time the ship arrives at the port and submits a mooring request until it gets pilot service to the berth. The existence of delays in Waiting Time and Approach time can cause losses to each ship and is quite detrimental for service users. Not only will costs increase, it will also have an impact on Waiting Time and Approach time for other ships. Therefore, to anticipate the long Waiting Time and Approach Time for ships that will dock at the port or wharf, PT Pelindo Multi Terminal Tanjung Intan Cilacap and the Cilacap Class II Port Authority and Harbormaster Office continue to make efforts to evaluate by maintaining operational service performance. in order to be able to provide effective services by maintaining queues of ships that will dock and ships that will leave, what is done by PT Pelindo Multi Terminal Tanjung Intan Cilacap and the Cilacap Class II Port Authority and Harbormaster Office in the 2022 period is very effective and has been going well, seen from the Waiting Time and Approach Time which is below the standard that has been set.